COMPARATIVE ANALYSIS OF PHYTOCHEMICAL, ANTIBACTERIAL, AND ANTIOXIDANT ACTIVITY OF DIFFERENT EXTRACTS OF AZADIRACHTA INDICA LEAVES - SHARMA, GAURAV; THAKUR, ANKITA; LAL, SOHAN; KUMAR NADDA, ROHIT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was the analysis of phytochemicals in various extracts of Azadirachta indica leaves, comparative evaluation of antibacterial activity of the various extracts of A. indica leaves against Escherichia coli and Staphylococcus aureus, and comparative evaluation of antioxidant activity in various extracts of A. indica leaves using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. Methods: Various extracts were prepared by crushing the samples. Antibacterial susceptibility test, various phytochemical tests for qualitative analysis, and DPPH radical scavenging assay for antioxidant activity were performed. Results: The result suggested that alkaloids, flavonoids, and terpenoids were present in all the four extracts. Tannins were absent in the ethyl acetate extract, and phenols were only present in the ethyl acetate extract. Sterols and phlobatannins were absent in all the four extracts. Saponins were only present in the aqueous extract, and amino acids were only present in the ethyl acetate extract. The bacterial strains S. aureus and E. coli were used against the different extracts of A. indica leaves, i.e., methanol, chloroform, ethyl acetate, and aqueous. Conclusion: The results suggested that bioactive compounds found in leaves of A. indica contribute to its pharmacological activities.